2012
DOI: 10.1155/2012/142087
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models as Tools to Investigate Antidiabetic and Anti-Inflammatory Plants

Abstract: Plants have been historically used for diabetes treatment and related anti-inflammatory activity throughout the world; few of them have been validated by scientific criteria. Recently, a large diversity of animal models has been developed for better understanding the pathogenesis of diabetes mellitus and its underlying inflammatory mechanism and new drugs have been introduced in the market to treat this disease. The aim of this work is to review the available animal models of diabetes and anti-inflammatory act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 99 publications
1
109
0
1
Order By: Relevance
“…On the other hand, numerous reports have demonstrated that inflammation, as an important defense mechanism, occurs in diabetic patients (41), which consequently leads to insulin resistance and initiates type II diabetes (42).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, numerous reports have demonstrated that inflammation, as an important defense mechanism, occurs in diabetic patients (41), which consequently leads to insulin resistance and initiates type II diabetes (42).…”
Section: Discussionmentioning
confidence: 99%
“…8 From the critical analysis of the result, administration of Agnimantha leaf and root kwatha (decoction) at the dose of /kg b.w orally showed moderate to significant decrease in the 1 st hour, similar to the standard drug, diclofenac. While in the 3 rd hour, the Agnimantha root group and the standard group showed moderate to significant decrease and the Agnimantha leaf group showed only mild non significant decrease of paw volume In the 6 th hour all the 3 groups showed significant decrease in the paw volume but the difference is the standard group showed high significant decrease, and the Agnimantha leaf and root group showed only moderate decrease in paw volume.…”
Section: Discussionmentioning
confidence: 99%
“…Cotton pellet implanted granuloma model is based on the foreign body granuloma that can provoke by subcutaneous implantation of pellets of compressed cotton in rats. The cotton pellets implanted in the intrascapular region induces a chronic inflammation process in which development of proliferative cells, monocyte migration, liquid accumulation, apoptosis, damage and so on will occur in the surrounding tissue of the pellets and these accumulations will produce a granulation tissue that covers the pellets 17 . During the repair process of nflammation, there is proliferation of macrophages, neutrophils, fibroblasts and multiplication of small blood vessels, which are the basic sources of forming a highly vascularised reddish mass, termed granulation tissue.…”
Section: Discussionmentioning
confidence: 99%